PM2.5 국가기준측정장비 선정을 위한 비교 측정 연구 - 이용환(Yong Hwan Lee); 박진수(Jin Su Park); 오준(Jun Oh); 최진수(Jin Soo Choi); 김현재(Hyun Jae Kim); 안준영(Joon Young Ahn); 홍유덕(You Deog Hong); 홍지형(Ji Hyung Hong); 한진석(Jin Seok Han); 이강웅(Gangwoong Lee) (한국대기환경학회지(국문), 2015)
To establish National Reference Method (NRM) for PM2.5, operational performance of 5 different commercial gravimetric-based PM2.5 measuring instruments was assessed at Bulkwang monitoring station from January 23, 2014 to February 28, 2014. First, physical properties, design, and functional performance of the instruments were assessed. Evaluation was carried out to determine whether operating method for the instruments and levels of QA/QC activities meet the data quality objectives (DQOs). To verify whether DQOs were satisfied, reproducibility of QA/QC procedures, accuracy, relative sensitivity, limit of detection, margin of error, and coefficient of determination of the instruments were also evaluated. Results of flow rate measurement of 15 candidate instruments indicated that all the instruments met performance criteria with accuracy deviation of 4.0% and reproducibility of 0.6%. Comparison of final PM2.5 mass concentrations showed that the coefficient of determination (R2) values were greater than or equal to 0.9995, and concentration gradient ranged from 0.97 to 1.03. All the instruments satisfied criteria for NRM with the estimated precision of 1.47~2.60%, accuracy of -1.90~3.00%, and absolute accuracy of 1.02~3.12%. This study found that one particular type of measuring instrument was proved to be excellent, with overall evaluation criteria satisfied. KCI Citation Count: 2